Assessing the impact of charcoal production activities on the Shea Nut tree vegetation cover - Calvin, Esagu John; Warsito, Budi; Hidayat, Jafron Wasiq; Gertrude, Akello; Paul, Gudoyi M; Ahmed, Kamil (Journal of Bioresources and Environmental Sciences, 2023)
Charcoal remains the main energy cooking source for urban dwellers in Uganda. The Shea Nut tree produces quality charcoal which is efficient and locally made. Therefore, it is facing increasing threats from the local communities so as to meet the mushrooming demand. The study analyses the state of the Shea Nut tree, drivers of charcoal production, predict Shea Nut tree vegetation coverage, and establish mechanisms for sustainable utilization and conservation of the Shea Nut trees in Kapelebyong District. Landsat images were classified using likelihood classification in ArcGIS and interviews were conducted whilst geospatial, Stata, and Nvivo tools were used for analysis. The findings reflect a sharp declining trend in the coverage of the shea Nut trees by 2.3% and 6% from 2002-2012 and 2012-2022 respectively. The major drivers include high demand from urban areas, the need for income, and unemployment. As a result, it is predicted that by 2032, the coverage will have reduced to only 713 hectares (7.3%) from 1277 hectares (10.6%) in 2022. Therefore, charcoal production with other land uses has greatly resulted in Shea Nut tree deterioration. The study recommends the use of alternative energy sources, the provision of alternative income-generating activities for the local communities, Government of Uganda through NFA needs to enforce the ways through which Shea Nut trees are managed and utilized in order to minimize illegal cutting.